Brazil's automotive and textile sectors during the Covid-19 pandemic: Crisis, repercussions and responses from the government, companies and labor unions - Bruno de Conti; Arthur Welle; Diógenes Moura Breda (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
In addition to the severe health crisis, the Covid-19 pandemic provoked one of the deepest socioeconomic crises in the history of capitalism. Yet, the economic structure of each country and the strength of the welfare state, along with the ability of the diverse governments to cope with the situation, resulted in very diverse outcomes. In particular, center and peripheral countries had very different policy spaces to deal with the crises. One of the important consequences of the pandemic for the world economy was the disruption of Global Value Chains (GVCs). The aim of this article is investigating the effects of the pandemic on the automotive and the textile industries in Brazil, as well as the responses from the national government, and from these sectors' companies and labor unions to this critical situation. Ultimately, it inspects if the pandemic and the so-called "coronacrisis" are provoking structural changes to Brazil's insertion in the international production networks of these two sectors. The methodology includes the analysis of data for the overall Brazilian economy and the two studied sectors (secondary data, but also our own estimations based on the National Household Survey); a review of the literature and the sectoral reports; and several interviews made with workers and managers in the two sectors, as well as policy makers. Despite the differences in the effects of the pandemic on both sectors, one commonality is the deepening of the precarity of working conditions, with increasing turnover in some subsectors, alternation of periods with no work and periods with very intense work and a decline in average incomes.
Keywords: F15; F62; L62; L67; O11; 330; Brazil; automotive industry; textile industry; Covid-19 pandemic; Global Value Chains